Analysis of sound emission using ternary blend fuel in compression ignition engine - Faheem Ahmed Solangi,; Liaquat Ali Memon,; Saleem Raza Samo,; Muhammad Ramzan Luhur, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Alternative fuel is considered to be suitable oils in diesel engines, which are well known for their ability to diminish lubricant oil debris and noise emissions. A minute research has been done to examine the long-term effects of using blend fuel. In this study, two blend fuels: diesel and waste cooking oil (DF95WCO5), and diesel, waste cooking oil and n-pentanol (DF65WCO20Pe15) were chosen and compared with diesel fuel (DF) to investigate the impact of these blends on noise emission in diesel engine. In order to evaluate the kinematic viscosity and density and determine the effect on sound pressure levels, lubrication oil samples were taken throughout the test at intervals of 20 hours. A literature review was done for the current work’s analysis of the literature on the noise emissions from diesel-waste cooking and n-pentanol fuel blends. When the engine was fueled with DF65WCO20Pe15 blend, the engine lubricating oil analysis revealed an extreme wear issue, decreased viscosity, and increased density values. The conclusion is that single cylinder diesel engines can use binary blend DF95WCO5 and ternary blend DF65WCO20Pe15 without any adjustments. DF65WCO20Pe15, in contrast to the reference fuel, achieved some superior outcomes.